Using parsed and annotated corpora to analyze parliamentarians' talk in Finland. (4th June 2021) - Andrushchenko, Mykola; Sandberg, Kirsi; Turunen, Risto; Marjanen, Jani; Hatavara, Mari; Kurunmäki, Jussi; Nummenmaa, Timo; Hyvärinen, Matti; Teräs, Kari; Peltonen, Jaakko; Nummenmaa, Jyrki
Abstract: We present a search system for grammatically analyzed corpora of Finnish parliamentary records and interviews with former parliamentarians, annotated with metadata of talk structure and involved parliamentarians, and discuss their use through carefully chosen digital humanities case studies. We first introduce the construction, contents, and principles of use of the corpora. Then we discuss the application of the search system and the corpora to study how politicians talk about power, how ideological terms are used in political speech, and how to identify narratives in the data. All case studies stem from questions in the humanities and the social sciences, but rely on the grammatically parsed corpora in both identifying and quantifying passages of interest. Finally, the paper discusses the role of natural language processing methods for questions in the (digital) humanities. It makes the claim that a digital humanities inquiry of parliamentary speech and interviews with politicians cannot only rely on computational humanities modeling, but needs to accommodate a range of perspectives starting with simple searches, quantitative exploration, and ending with modeling. Furthermore, the digital humanities need a more thorough discussion about how the utilization of tools from information science and technologies alter the research questions posed in the humanities.